2013
DOI: 10.5231/psy.writ.2013.2106
|View full text |Cite
|
Sign up to set email alerts
|

Felicidad y actividad física en personas mayores

Abstract: El principal objetivo de este estudio fue explorar la felicidad -presente y pasada-de personas mayores de 65 años, así como la relación que la práctica de Actividad Física pudiera tener con ella. Los participantes cumplimentaron voluntariamente un cuestionario de datos sociodemográficos, el Cuestionario de actividad Física General en versión española y la Escala de Felicidad. Los resultados muestran que la felicidad actual de los mayores es inferior a la felicidad pasada. Además, se demuestra que la práctica a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Only the current happiness score was used in this study. This self-report has been previously used in research conducted in older adults [ 19 , 20 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the current happiness score was used in this study. This self-report has been previously used in research conducted in older adults [ 19 , 20 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have found that as people grow old, their HB and LS decrease [ 18 , 19 , 20 , 21 , 22 , 23 ]. In addition, in general, evidence supports that higher levels of SWB (i.e., HB and LS) are linked with more positive indicators of psychological, physical, interpersonal, and socioeconomic functioning at both the personal and societal levels [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ibáñez-Pérez, Martínez-Moreno and López-García indicate that the benefits of the older adult population being physically active have been remarked in the research literature for a long time, since physical activity has a very important impact on the quality of life [5]. This participation helps to avoid the feeling of isolation that can occur in older adults [6], by positively affecting their happiness and well-being [7].…”
Section: Introductionmentioning
confidence: 99%
“…En general, se encuentra que las personas mayores que realizan deporte independientemente del tipo de ejercicio practicado obtienen mejorías en su estado de ánimo y bienestar psicológico (Bohórquez et al, 2013;De-Juanas et al, 2013;Rodríguez-Hernández et al, 2014). En concreto, influye positivamente sobre su autoestima, mejora la autoeficacia y la depresión (García et al, 2012;Gallego et al, 2012).…”
Section: Discusión-conclusionesunclassified